DESKRIPSI KESALAHAN STRUKTUR BERPIKIR SISWA SMP DALAM MENYELESAIKAN MASALAH GEOMETRI SERTA DEFRAGMENTINGNYA: SUATU STUDI KASUS - Taufiq Hidayanto; Subanji Subanji; Erry Hidayanto (Jurnal Kajian Pembelajaran Matematika, 2017)
It is revealed that as a compulsory mathematic subject for junior high school students, most students are struggling to solve geometric problem. As an effort to fix this condition, this article describes mistakes of junior high school students’ structural thinking in solving geometric problem. Subjects’ mistake were assessed by Subanji’s (2015) theory of conceptual construction mistake and mathematical problem solving. Researcher then defragmented subjects’ thinking structure in order to solve problems effectively. The result shows that subjects experienced miss logical construction and construction gap. Miss logical construction occurred because students’ logical mistake in solving the problem, while the construction gap happened due to certain incomplete schemes in subjects’ problem solving thinking structure. Defragmenting was conducted by assessing mistakenly constructed scheme. Then, unconstructed scheme was revealed. When scheme had considered as sufficient, the constructed scheme were knitted into an interconnected scheme and subjects’ thinking structure became complete. Decomposition of incorrect structured schemes used cognitive conflict, while scheme and scheme knitting applied scaffolding.